Protection of geographical indications in Peru - Arana Courrejolles, María del Carmen (2020)
This article intends to introduce a reflection regarding the protection of Geographical Indications in Peru; we identify the relevant norms, the Andean Prejudicial Interpretation and its application in different cases. To this end, this investigation will focus on the cases of Peru and Colombia, with the validity of Decision 486, to identify the form and content in which the competent Administrative Authority resolved certain trademark applications, in relation to absolute registration impediments of marking of signs referring to a geographical indication or origin of the place of origin contained in literals e), i), l) of article 135 of Decision 486.